(untitled) (Encuentros, 2021)
This article, which studies the poetry book Pájaro amargo, by José Ramón Mercado, seeks to show the character of a “damaged” family experience in the context of the Colombian Caribbean, after which the figure of a father who develops an abject relationship with his line is questioned. For this, a hermeneutical and comparative methodology was used, based, especially, on the psychoanalytic reading of the parent, by Julia Kristeva; by Paul Ricœur, on forgiveness and reconciliation, and by Laura Scarano, on the relationship between expression, subjectivity, writing and life. It is concluded that literature contains an exhibition not only artistic, but also ethical and moral, expressed through symbols that reveal the duels with fatherhood, the result of a painful memory of the past that explodes in the lyrical writing of the present as a settling of accounts